RESEARCH OF CHARACTERISTICS OF HEAT AND MASS TRANSFER AT THE INTRODUCTION OF TECHNOLOGY OF STEPS FUEL BURNING ON THE BKZ-75 BOILER OF THE SHAKHTINSKAYA TPP - Safarik, P.; Bolegenova, S.A.; Tuyakbaev, A.A.; Maximov, V.Yu.; Nugymanova, A.O.; Shortanbaeva, Zh.K. (Academic Scientific Journal of Computer Science, 2020)
This article presents computational experiments on the introduction of step-by-step fuel combustion (OFA) technology using the example of the combustion chamber of the BKZ-75 boiler at the Shakhtinskaya TPP. OFA technologies are based on the separation of the supplied oxidizing agent into the combustion space in such a way as to reduce the amount of fuel NOx in the area of the burners by reducing excess air, and the amount of thermal NOx by reducing the temperature of the flame in the area of the OFA injectors. Using computer simulation methods, various modes of supplying additional air to the combustion chamber of the BKZ-75 boiler through OFA injectors were studied: OFA=0% (basic version), OFA=10%, OFA=18%. As a result of computational experiments, the distributions of the concentrations of carbon monoxide CO and nitrogen dioxide NO2 were obtained over the entire volume of the combustion chamber. The most important result of the introduction of staged fuel combustion (OFA=18%) is a decrease in the concentration of nitrogen dioxide NO2 at the outlet of the combustion chamber by 25% and carbon monoxide CO by 36%. The results allow us to conclude that the introduction of Overfire Air (OFA) technology has a positive effect on the heat and mass transfer in the combustion chamber and minimizes emissions of harmful substances.